Large Scale Engineering Systems – Insight on Desalination for Agriculture in Saudi Arabia. Issue 1 (13th September 2016) - Doufene, Abdelkrim; Ishimatsu, Takuto; Alhassan, Abdulaziz; de Weck, Olivier; Strzepek, Kenneth; Alsaati, Adnan
Abstract: As agriculture water demand in Saudi Arabia is fully met through underground water resources, and their levels of depletion are not sustainable, we evaluate in this paper the concept of "Desalination for Agriculture" at a national level. We discuss a case study and some results using a graph‐theoretic framework called the Interdependent Network Flow with Induced Internal Transformation (INFINIT) model. This model can be used to optimize the flow of resources and placement of new facilities (and expansion or retirement of existing facilities) at the individual facility level over multiple dimensions of geographical networks. This model can solve an optimization problem considering both spatial and temporal dimensions: a spatial dimension, that is, where a new infrastructure should be invested at a given time; and a temporal dimension, that is, when a new infrastructure should be invested. We conclude with a set of perspectives.